2014
DOI: 10.3390/geosciences4010031
|View full text |Cite
|
Sign up to set email alerts
|

Critical Factors Controlling Pd and Pt Potential in Porphyry Cu–Au Deposits: Evidence from the Balkan Peninsula

Abstract: Porphyry Cu-Au-Pd±Pt deposits are significant Au resources, but their Pd and Pt potential is still unknown. Elevated Pd, Pt (hundreds of ppb) and Au contents are associated with typical stockwork magnetite-bornite-chalcopyrite assemblages, at the central parts of certain porphyry deposits. Unexpected high grade Cu-(Pd+Pt) (up to 6 ppm) mineralization with high Pd/Pt ratios at the Elatsite porphyry deposit, which is found in a spatial association with the Chelopech epithermal deposit (Bulgaria) and the Skouries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…This study has confirmed that the PGE in Skouries are associated with the main vein stage of Cu deposition in this deposit. This agrees with work by Eliopoulos and Economou-Eliopoulos (1991), Eliopoulos et al (2014), who analysed whole rock samples for PGE content and found the potassic alteration zone to have Pd contents of 60-610 ppb and Pt contents of 5-150 ppb. Earlier work suggested that precious metal tellurides were formed in relatively shallow, cool environments, and that the PGE may have been redistributed during a late hydrothermal event Mutschler et al, 1985).…”
Section: Pgm In the Skouries Depositsupporting
confidence: 80%
See 4 more Smart Citations
“…This study has confirmed that the PGE in Skouries are associated with the main vein stage of Cu deposition in this deposit. This agrees with work by Eliopoulos and Economou-Eliopoulos (1991), Eliopoulos et al (2014), who analysed whole rock samples for PGE content and found the potassic alteration zone to have Pd contents of 60-610 ppb and Pt contents of 5-150 ppb. Earlier work suggested that precious metal tellurides were formed in relatively shallow, cool environments, and that the PGE may have been redistributed during a late hydrothermal event Mutschler et al, 1985).…”
Section: Pgm In the Skouries Depositsupporting
confidence: 80%
“…7; Sotnikov et al, 2001;Tarkian and Stribrny, 1999). These ratios either reflect the relative PGE contents in the source magma (Economou- Eliopoulos and Eliopoulos, 2000), or the fractionation of PGE in the mineralising fluid (Eliopoulos et al, 2014). PGE-enriched porphyry deposits globally have very similar Au/(Pd + Pt) of ∼90 and Pd/Pt of ∼10 (Fig.…”
Section: Pgm In the Skouries Depositmentioning
confidence: 99%
See 3 more Smart Citations